Double-Low Dose Protocol of Computed Tomography Pulmonary Angiography (CTPA) in the Diagnosis of Pulmonary Embolism: A Feasible Approach for Reduction of Both Contrast Medium and Radiation Doses - Aldosari, Sultan; Al-Moudi, M.; Sun, Zhonghua (Openventio, 2017)
This article discusses a hot topic on double low-dose protocol of computed tomography pulmonary angiography (CTPA) in the diagnosis of pulmonary embolism, with a special focus on a recent paper published in the British Journal of Radiology about the feasibility of this technique. Three aspects will be discussed in this review: First, both kVp and contrast medium can be reduced without affecting image quality when compared to the standard CTPA protocol; second, a low-pitch protocol is comparable to the high-pitch spiral image acquisition with similar image quality achieved, but at lower radiation dose; and finally, the double low-dose CTPA protocol can achieve diagnostic images in patients with body mass index up to 35 kg/m2.